2021
DOI: 10.1111/jsr.13274
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and obstructive sleep apnea: Current perspectives and novel technologies

Abstract: Summary Obstructive sleep apnea (OSA) is a highly prevalent condition, resulting in recurrent hypoxic events, sleep arousal, and daytime sleepiness. Patients with OSA are at an increased risk of cardiovascular morbidity and mortality. The mechanisms underlying the development of cardiovascular disease in OSA are multifactorial and cause a cascade of events. The primary contributing factor is sympathetic overactivity. Heart rate variability (HRV) can be used to evaluate shifts in the autonomic nervous system, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 92 publications
1
43
0
Order By: Relevance
“…Patients with OSAHS are at an increased risk of cardiovascular morbidity and mortality. The mechanisms underlying the development of cardiovascular disease (CVD) in OSAHS are multifactorial and cause a cascade of events 13 . Sympathetic activation, systemic inflammation, intermittent hypoxia, and oxidative stress are the main intermediary mechanisms linking OSAHS and CVD 13‐15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with OSAHS are at an increased risk of cardiovascular morbidity and mortality. The mechanisms underlying the development of cardiovascular disease (CVD) in OSAHS are multifactorial and cause a cascade of events 13 . Sympathetic activation, systemic inflammation, intermittent hypoxia, and oxidative stress are the main intermediary mechanisms linking OSAHS and CVD 13‐15 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the development of cardiovascular disease (CVD) in OSAHS are multifactorial and cause a cascade of events 13 . Sympathetic activation, systemic inflammation, intermittent hypoxia, and oxidative stress are the main intermediary mechanisms linking OSAHS and CVD 13‐15 . OSAHS may contribute to the vascular endothelial dysfunction and the formation of atherosclerotic plaque 16‐17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, an increase in SDNN24 of 1% results in an lower risk of heart failure of about 1% [5]. It was also found that the alteration in cardiac autonomic function is a predictor of several other individual health problems, such as diabetes [6], hypertension [7], and sleep quality [8]. Moreover, one of the last findings about SDNN24 is that changes in autonomic nervous system function that can be estimated by change in heart rate variability (HRV) have also been found to be a predictor of infection and, in particular, for the diagnosis of COVID-19 and its related symptoms [9][10][11].…”
Section: Introductionmentioning
confidence: 99%